The Past, Present, and Future of Myocardial Revascularization - Budi Yuli Setianto (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
One of the important diagnostic modalities in cardiology is cardiac catheterization, which is onetool for myocardial revascularization. This examination is particularly useful in the aspect ofcardiac hemodynamic evaluation, among other utilities. This review describes the advance ofcardiac catheterization from the beginning of its discovery to future development.